Extraction of high-quality genomic DNA and identification of different DNA barcoding markers for chickpea (Cicer arietinum L.) - Umavathi Saraswathi; Lakshmanan Mullainathan (Universitas Prof. Dr. Hazairin SH, 2020)
The genetic studies of individual plants, especially self-pollinated species like chickpea need to be evaluated at the DNA level with the help of molecular markers for identifying genetic variations among the plants. High-quality DNA extraction is a prerequisite for genetic studies. Extraction of intact genomic DNA with high – molecular mass is essential for the study of many molecular biology applications like Polymerase Chain Reaction, endonuclease restriction digestion, southern blot analysis, and also for the construction of a genomic library. Several plant DNA extraction methods are available, even though the DNA isolation methods that give good yield employing both quantity and quality is quite difficult especially for self-pollinated crops like a chickpea. This work was focused on developing a standard protocol for the extraction of genomic DNA and identifying different barcoding markers. The result revealed that the CTAB extraction method with slight modification in protocol had been optimized for DNA isolation. The purified DNA, which was isolated through the CTAB method, had excellent spectral qualities and is efficiently digested by a restriction endonuclease, and is found to be more suitable for long-fragment PCR amplification. DNA barcoding is considered as a promising tool because it provides a practical and standard identification of plants. The isolated DNA sample was processed with a classical DNA barcoding approach by amplifying and sequencing with a universal primer. According to the result, among the different barcoding markers studied, the RbcL and Mat K were found to given the best result for molecular species identification in chickpea.